Local Wisdom Values in the Management Based on Local Democracy Model - Wesna Astara, I Wayan (Opción, 2019)
This article discusses specifically the customary law politics of customary village in the implementation of local government policy in Bali and its implementation in Kuta-Bali Indigenous village via comparative qualitative research methods. As a result, in its original autonomy, the indigenous villages in Kuta do not require the state law and state law-based democratic model in organizing their village heads election. In conclusion, local democracy, especially in the selection of the Kuta-Bali traditional Bendesa, is determined by the value of local wisdom such as customary law, Desadresta, Desamawacara, and the State of Mawatata.